PENGARUH KEPEMIMPINAN DAN K3 TERHADAP KINERJA KARYAWAN BAGIAN TEKNIK PT. PLN (PERSERO) UPJ-SEMARANG - Riana Aprilia; Apriatni Endang Prihatini (Universitas Diponegoro, 2016)
Engineering division of PT. PLN (Persero) UPJ of Central Semarang is a company with responsibility towards public services in the field of electricity. The achievement of good public services is determined by employees’ abilities to do their jobs. Currently, Engineering division of PT. PLN (Persero) UPJ of Central Semarang is facing some problems related to expected performance targets which have not been achieved. It is proven by the level of transformer damage which breaks the tolerance limit. Therefore, the purpose of this study is to determine the effect of Kepemimpinan, Kesehatan dan Keselamatan Kerja (K3) – Leadership, Health and Safety – on Employee Performance of Engineering division of PT. PLN (Persero) UPJ of Central Semarang. This study is an explanatory research. The population in this study were the employees of Engineering division of PT. PLN (Persero) UPJ of Central Semarang consisting of 50 respondents as the samples. The sampling technique used was census. The results show that the variables of leadership and K3 separately or together affect the performances of employees. Based on assessment results from each employee, employee performance as an individual is in a very good category. Meanwhile, based on assessment results from leaders, the employee performance as a group level or an engineering division performance has not been able to achieve expected performance targets. Thus, there are some differences of employee performance assessment results from the leaders and from the individual. Individual performance does not automatically create a group or division performance. Therefore, leaders’ roles are needed to improve employees' understanding on performance standards which are expected by the company. Leadership and K3 program variables are the variables which can affect the employee performance, so that the roles of leaders and K3 program need to be continuously developed.